The Relationship Between Work Shifts And Work Stress Among Nurses In The Maternity Ward At Permata Bunda Hospital - Lufianti, Anita; Azizah, Nimas Nur; Fitriani, Fitriani (INDOGENIUS, 2025)
Background and Objective: Stress is a symptom of the biggest disease of the modern century that is often experienced by nurses in hospitals. Stress in the workplace is where employees encounter conditions of overwork, low levels of job satisfaction. One of the causes of work stress is work shift arrangements. The data obtained is that nurses complain of work stress due to the continuing shift schedule or nurses replacing their colleagues' work shifts due to the lack of manpower in the room. The purpose of this study was to determine the relationship between work shifts and nurses' work stress in the maternity ward of Permata Bunda Hospital Purwodadi. Method: This is quantitative research with a cross sectional research method, with a correlation approach, the sampling technique used total sampling, which amounted to 26 respondents.  Results: The test results using spearman rank between work shifts and nurses' work stress, obtained p value (0.000) < α (0.05) which means H0 is rejected and Ha is accepted. With a correlation result of 0.723, it’s concluded that there is a significant relationship between work shifts and work stress. Conclusion: There is a relationship between work shifts and nurses' work stress, meaning that there is a positive correlation between work shifts and work stress. This means that the more inappropriate the work shift, the heavier the nurse's work stress.